Możliwości badań porównawczych nad ruchliwością społeczną - Żyromski, Marek (Wydział Prawa i Administracji UAM, 1986)
The task of the article is a presentation of possibilities, of comparative research of social mobility. Categories of social mobility were introduced for the analysis of modern industrial societies. But the discussed phenomenon was also observed in the pre-industrial societies. Presentation of the basic categories of social mobility is the departure point for the discussion in the article. Presentation basic lilterature of the subject dated back to the pre-war Pitrim Sorokin works ought to indicate shortcomings of various handling of social mobility. The researchers too often identify it merely with the social advancement discussed only in categories of profession, omitting the group aspect of the phenomenon, not referring their analyses to the theory of society as a whole. The article discusses a number of indices of social mobility. Various examples of social mobility observed in the old societies are also quoted. It can prove the weight of that research, rarely taken up in sociology, concentrating itself on modern times. A sociological reflection on older societies has to consider a different conditioning. A problem can be posed by representativeness of samples, the information retained concerns mostly the upper classes. Not all the categories of social mobility can be accounted for the analysis of the pre-industrial societies. Nevertheless, the basic questions are still applicable: relating mobility to the theory of social structure, considering a number of straficational variables, mobility channels, differentiation between inter and intragenerational mobility. The research on mobility in older societies allows to learn their structure and dynamics and to introduce new solutions to the sociological theory of stratification and social mobility.
A Question of Comparative Research on Social Mobility